Analysis of the Influence of Digital Marketing and Product Quality on Customer Loyalty - Julie Abdullah; Uli Wildan Nuryanto; Pandu Adi Cakranegara; Firstianty Wahyuhening Fibriany; I Gusti Ngurah Agung Dewantara Putra (Quantitative Economics and Management Studies, 2022)
The purpose of this study was to analyze the effect of digital marketing and product quality on customer loyalty. This research is a quantitative research with a descriptive and verification approach. From the research that has been done, it is obtained that the value of t count > t table so that digital marketing and product quality have a positive and significant effect on customer loyalty. The R-square value obtained is 0.852 which states that digital marketing and product quality variables affect customer loyalty by 85.20% and the remaining 14.80% is influenced by other variables.